Authenticity of the Deed of General Meeting of Shareholders (GMS) Conducted on the Basis of Cyber Notary During the Covid-19 Pandemic - Melyana Puspita Wati; Sulistyandari Sulistyandari; Siti Kunarti (Journal of Social Research, 2023)
The Covid-19 pandemic that has hit the entire population of the world in recent times has had a significant impact on human life. People around the world have to start getting used to adapting to new habits due to the presence of the Covid-19 virus. This is also the case in Indonesia, one of the government's policies is to issue a policy to carry out all activities at home, starting from work, school, and the obligation to limit activities outside the home or even limit meeting people. This policy also has an impact on the performance of the Notary, where the Notary in making an authentic deed is obliged to deal with the parties. The solution related to this then emerged a policy regarding cyber notary, where in making an authentic deed the Notary does not have to deal with the client and the deed can be signed electronically. This policy raises pros and cons, including the authenticity of the GMS deed which is carried out using the cyber notary method. This study uses a normative juridical method with a qualitative approach. The purpose of this study is to find out about the authenticity of the deed of the GMS made with a cyber notary during the covid-19 pandemic. The result of this research is that the deed of the GMS made using the cyber notary method is an authentic deed if it is made on the basis of the lex specialist derogate legi generali principle. it is in Article 77 paragraph (1) in conjunction with Article 77 paragraph (4) of the Limited Liability Company Law. After the parties have signed the deed of the GMS, the Notary on the basis of Article 11 of the ITE Law and the fulfillment of the lex specialist principle, the deed can be used as perfect evidence in court.